POTENTIAL AND DEVELOPEMENT STRATEGY OF MANGROVE ECOTOURISM IN SUNGAI RAWA VILLAGE SIAK REGENCY RIAU PROVINCE - Oktarina, Ayu; Mulyadi, Aras; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Mangrove ecotourism is an effort to maintain and utilize mangroves. This research was conducted in Sungai Rawa Village, Siak Regency, Riau Province, in September 2019. The objectives of this study were to: 1). Knowing the potential of mangrove ecosystems in Sungai Rawa Village to be developed into a mangrove ecotourism destination, 2). Develop strategies for developing mangrove ecotourism in Sungai Rawa Village. The method used in this study is a survey method. The sampling points and the respondents were determined by the purposive sampling method. The mangrove forest of Sungai Rawa Village has the potential to be developed as a mangrove ecotourism area with good ecological conditions of the mangrove forest, has a high diversity of biota, research and conservation potential as well as a high level of security and hospitality for the community. Community participation in the development of ecotourism in Sungai Rawa Village is classified as low with an IPR value of -0.03 and Mean calculated value of 1.99 while community perceptions about ecotourism development in swamp river villages are high with an IPR value of 2.77 and an average value at 26.65. Based on stakeholder perceptions of the development of Sungai Rawa Village ecotourism is appropriate or feasible to be developed as an ecotourism area. Strategy in developing mangrove ecotourism in Sungai Rawa Village is to implement an aggressive strategy (Growth Oriented Strategy) by prioritizing SO strategies, namely: 1) Establishing mangrove forest areas in Sungai Rawa Village as a conservation area, 2) Increasing access to a wider market, 3) Building collaboration with related agencies and institutions. Keyword: Siak, Ecotourism, Mangrove